Evaluation of occupational safety and health management system implementation at Lasinrang Pinrang Hospital - Ridwan, Ridwan; Nadirah , Nadirah; Aswani, Irma; Muslimin , Muslimin; Tinta, Yulis (Institute Of Computer Science (IOCS), 2025)
The Occupational Safety and Health Management System (OSHMS) in hospitals is designed to manage workplace safety and health risks to create a safe, efficient, and productive environment for hospital personnel, patients, visitors, and the surrounding community. Based on data from 2024, Lasinrang Pinrang Regional General Hospital recorded 3 occupational accident (KAK) cases, including 1 needle stick injury and 2 chemical spills, while in 2025, there was still 1 reported case. This study aims to evaluate the implementation of the OSH Management System at Lasinrang Pinrang Regional General Hospital in 2025. The research employed a qualitative descriptive approach using interviews, observations, and document analysis as data collection techniques. The results indicate that the implementation of OSHMS at Lasinrang Pinrang Regional General Hospital has not been fully optimized, primarily due to limited human resource capacity and a lack of understanding among staff regarding OSHMS procedures and policies. From a theoretical perspective, this study contributes to the understanding of the critical role of human resources in the effective application of hospital-based OSH management systems. Practically, the findings highlight the need for systematic capacity building, structured supervision, and institutional commitment to continuous OSH improvement. Strategically, it is recommended that the hospital management develop a comprehensive OSH roadmap supported by adequate budget allocation, regular training, and performance evaluation mechanisms. These measures will strengthen the institutionalization of OSH culture, enhance compliance with national safety standards, and ensure sustainable implementation of the OSH Management System within the hospital environment.